Rāingān chabap sombūn khrōngkān songs̄œm sētthakit ph̨ōphīang læ prachāsangkhom, Ph̨ō. S̨ō. 2542-2543 (Sathāban Phatthanā Sīȳæk ʻIndōčhīn, 2000)
Research on sufficient economy and civil society development by implementing social mapping and networking in the lower north provinces of Thailand.